Rhyme and Word Placement in Storybooks Support High-Level Verb Mapping in 3- to 5-Year-Olds - Read, Kirsten; Quirke, Jacqueline (Frontiers in Psychology, 2018)
High-level verbs can be especially challenging for young children to initially map to meaning. This study manipulated the format of a storybook designed to support such verb learning from shared reading. We tested whether 3- to 5-yr-olds (n=38) could remember the referents of eight new verbs when presented as essential actions within a narrative story but with differences in placement. Children were randomly assigned to either a rhymed condition, in which target verbs were heard at the end of rhyming stanzas making them maximally appreciable, or a control condition, where the verbs were presented in the same story, but not in final position or within a rhymed stanza. After hearing the story, each child was given three sets of retention questions testing their identification, demonstration, and production of the target verbs. Children identified and successfully demonstrated more target verbs in the rhymed condition than the control condition, and only in the rhymed condition did children’s initial verb mappings exceed chance. No differences between conditions were found in children’s ability to produce the target verbs, in part because of how often they reverted to more generic terms to describe the actions in the story. Nonetheless, these findings support the hypothesis that giving children maximal support within a storybook reading context can facilitate an initial grasp on challenging verbs.